2019
DOI: 10.1021/acsanm.9b00091
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis and Antifungal Activity of Nontoxic Silver-Loaded Hydroxyapatite Nanocomposites against Candida Species

Abstract: The impact of fungal diseases and the development of antimicrobial agents against pathogenic fungi have emerged as a main global healthcare challenge. In this study, the antifungal activity of silver-loaded hydroxyapatite (Ag/HAP) nanocomposites (NCs) with different Ag content synthesized by a one-pot microwave-assisted solvothermal method was evaluated against sensitive and resistant Candida species. The NCs’ composition and morphology were characterized by X-ray diffraction, field emission scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…Therefore, development of new broad spectrum drugs is necessary for control of Candida infections (Nett et al ; Yapar ). In our study, C. albicans showed dose dependent susceptibility towards AgNPs with MIC of 4 µ g ml −1 , which is lower than earlier reports (Panáček et al ; Kulatunga et al ; Gottardo et al ). It was suggested that anticandidal activity of AgNPs is due to the disruption of cell membrane integrity (Kim et al ).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Therefore, development of new broad spectrum drugs is necessary for control of Candida infections (Nett et al ; Yapar ). In our study, C. albicans showed dose dependent susceptibility towards AgNPs with MIC of 4 µ g ml −1 , which is lower than earlier reports (Panáček et al ; Kulatunga et al ; Gottardo et al ). It was suggested that anticandidal activity of AgNPs is due to the disruption of cell membrane integrity (Kim et al ).…”
Section: Discussioncontrasting
confidence: 81%
“…Chemically synthesized AgNPs exhibits low MIC values along with high toxicity and low stability (Pal et al 2007;Kittler et al 2010;Pereira et al, 2014). Recently, anticandidal activity of rod-shaped silver loaded hydroxyapatite nanocomposites has been reported with MIC of 125 µg ml À1 against C. albicans (Gottardo et al 2019). However, it is important to note that, till date, there is only one report available on antifungal activity of bacteriogenic AgNPs against C. albicans (Lateef et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in resulting survival plots were evaluated using the Mantel-Cox test (Log-rank method) using the GraphPad Prism 5 software. The EO-loaded NLC formulations, at their respective concentrations tested, were considered toxic when they were able to kill at least 50% of larvae in a period of 5 days postinjection, following the protocol of Gottardo et al (2019) [36].…”
Section: In Vivo Toxicity Assaymentioning
confidence: 99%
“…The impact of bacterial disease and the promotion of effective antibacterial agents to combat pathogenic diseases have appeared as a serious global healthcare challenge. [1] To overcome such a challenge, antibacterial agents have been invented, and efforts are being made to invent more new antibacterial agents. Parallel to their invention and development, researchers are attempting to confirm the effectiveness of existing agents.…”
Section: Introductionmentioning
confidence: 99%